2000
DOI: 10.1093/ajcn/72.5.1128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fructose on plasma lipids in healthy subjects

Abstract: Dietary fructose was associated with increased fasting and postprandial plasma triacylglycerol concentrations in men. Diets high in added fructose may be undesirable, particularly for men. Glucose may be a suitable replacement sugar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
4
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(197 citation statements)
references
References 42 publications
7
179
4
7
Order By: Relevance
“…Regarding concentrations of serum triglycerides, the results are controversial; in some studies dietary fiber has been shown to have no effect on the concentration of serum triglycerides (Vuksan et al, 1999(Vuksan et al, , 2000, whereas in some other studies a decreasing effect of dietary fiber has been reported (Chandalia et al, 2000). The most commonly reported negative effect of fructose on serum lipid profile has been the increased concentration of serum triglycerides ( Bantle et al, 2000). This effect was not seen in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…Regarding concentrations of serum triglycerides, the results are controversial; in some studies dietary fiber has been shown to have no effect on the concentration of serum triglycerides (Vuksan et al, 1999(Vuksan et al, , 2000, whereas in some other studies a decreasing effect of dietary fiber has been reported (Chandalia et al, 2000). The most commonly reported negative effect of fructose on serum lipid profile has been the increased concentration of serum triglycerides ( Bantle et al, 2000). This effect was not seen in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…This is E20 times lower than mean intakes in the United States, in which approximately 9% of daily energy is derived from fructose. 135 High intakes of fructose have been implicated in the development of dyslipidemia and obesity. 131,136 High intakes of dietary fructose induce hyperlipidemia in rodents, 132 but studies on the effect of fructose intake on plasma lipids in adult humans are equivocal.…”
Section: Ldl Particle Sizementioning
confidence: 99%
“…Several have shown an effect of a high fructose intake on plasma lipids, particularly increased triglyceride concentrations, 137,138 but others have not. 135,139 The dietary determinants of LDL particle size in adults and children are uncertain. Several studies have shown that short-term high carbohydrate diets lead to a reduction in LDL particle size, [140][141][142] but they investigated only total carbohydrate intake and not specific types of carbohydrates.…”
Section: Ldl Particle Sizementioning
confidence: 99%
“…Disparate findings have been reported in this regard, with some studies showing positive associations between higher fructose consumption and plasma lipids (11,12) and blood pressure (13) and others showing no relationship (14,15). In children with diabetes, one small, short-term feeding trial was done showing no significant effect of high dietary fructose feeding on plasma lipids (16).…”
Section: Introductionmentioning
confidence: 89%